Synthesis of new triazole fused imidazo[2, 1-b]thiazole hybrids with emphasis on Staphylococcus aureus virulence factors. Issue 19 (1st October 2019) - Shareef, Mohd Adil; Sirisha, Kanugala; Sayeed, Ibrahim Bin; Khan, Irfan; Ganapathi, Thipparapu; Akbar, Syed; Ganesh Kumar, C.; Kamal, Ahmed; Nagendra Babu, Bathini
Graphical abstract: Abstract: A series of new triazole fused imidazo[2, 1- b ]thiazole hybrids (9a – u ) were designed, synthesized and evaluated as antimicrobial agents. Compounds 9c, 9d, 9e, 9j and 9l showed promising broad spectrum antimicrobial activity. Further, compound 9c exhibited significant anti-biofilm activity with single and mixed biofilm disruption demonstrated by Field Emission Scanning Electron Microscope (FE-SEM). Furthermore, molecular docking studies revealed that they interact with the virulence factor, Staphylococcus aureus dehydrosqualene synthase (CrtM) (PDB ID: 2ZCS). Overall, the findings suggest compound 9c as potential lead for further development of novel antibacterial and anti-biofilm agents.